Influence Of Quality Of Work Life, Organizational Culture And Workload On Teacher Performance - Puspitasari, Dahlia Rineva; Suharto, Nugraha; Supiani, Supiani; Saepulloh, Isep; Pribadi, Luthfi Audia; Lase, Destin Ricardo; sari, Herlina permata (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The quality of work life influences performance, meaning that the higher the quality of work life can improve performance. Performance is the basis for achieving the goals of an organization. This research aims to look at the influence of quality of work life, organizational culture and workload on teacher performance. The research was carried out using a quantitative approach where quantitative data relies on a population and withdrawal techniques, and uses questionnaires for data collection. The method used in the research is the regression analysis method. The research population was all teachers at SDN schools in Kertasari District, represented by teachers with ASN and PNS status. Number of teachers in 41 schools. So if we describe the total number of teachers, there are 135 who will become population and sample data or will become respondents in further research. When conducting this research, when collecting data, you can use field studies to come directly to the research object. Then by distributing and giving questionnaires directly to respondents. Data analysis used to determine the influence of independent variables and dependent variables is descriptive statistical analysis, validity test, reliability test, simple linear regression analysis, followed by a significant test, namely the t test. This research explains the influence of Quality of work life, organizational culture, workload on the performance of elementary school teachers in Kertasari District. From the problem formulation presented in chapter 1 and the results of data testing that has been carried out as well as the discussion presented in chapter IV previously, the following conclusions can be drawn. Simultaneously, the calculated F-value is 2.967 and the F-table value is 3.18, so that the F-count value (8.945) < F-table (2.67) with a significant value of 0.000 < 0.05, then, H0 is rejected and H4 is accepted. It can be concluded that Quality of work life, work culture and workload together have a significant influence on the performance of SDN teachers in Kertasari District.